THE IMPACT OF COLIN KAEPERNICK'S PROTEST ON PUBLIC PERCEPTION OF ATHLETE ACTIVISM - Restu, Pandu Wiguna; Susilastuti, Dewi Haryani (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This article presents the influence of Colin Kaepernick’s protest on the public's perception of athlete activism. This will entail doing a thorough examination and analysis of pertinent previous research related to the NFL game that had similar activities to those of Colin. The primary data comprises the results of American Football matches, the performances during NFL matches, the pre-game, which includes the kneeling protest by various sportsmen, and noteworthy findings from earlier studies. The study will undergo a comprehensive examination and analysis. This involves analyzing the intricate correlation between race, racism, athlete activism, and how these interconnections reflect broader societal inequalities and power dynamics. There are three keyways in which researching the linkages between professional football and social movements sheds light on the interplay of sport, politics, and culture. In addition, this article shows some of the various ways that professional football players have utilized the game for purposes other than just earning money and enjoying a love of the game. In this instance, the NFL and the press got along well throughout the decade, therefore, the public's perception of the NFL’s responses to social movements was largely determined by the press's coverage of the events.